Blended Learning for Character Education: Integrating Tri Hita Karana Wisdom to Develop Graduate Competencies Aligned with SDGs - Astawan, I Gede; Utama, I Dewa Gede Budi; Paramartha, Wayan Eka; Abdurahman, Ayi; Maidin, Siti Sarah (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study examines the effectiveness of a technology-enhanced character education model based on the Balinese Tri Hita Karana philosophy in developing primary students’ competencies aligned with SDG 4. Using blended learning, it addresses gaps in research on culturally grounded technology integration in character education. Methodology: This quasi-experimental study involved 92 fifth-grade students from four primary schools in Karangasem, Bali, comparing a Technology-Enhanced Tri Hita Karana Character Education Model with conventional instruction. Using LMS, digital portfolios, gamification, and learning analytics, competencies were assessed through questionnaires, portfolios, and observations, with data analyzed using t-tests, ANCOVA, and thematic analysis. Main Findings: The experimental group demonstrated significantly higher graduate competency scores (M=81.89, SD=9.78) compared to the control group (M=70.02, SD=10.02), t(90)=5.98, p<.001, Cohen's d=1.25, indicating a large effect size. Analysis of digital portfolio data revealed enhanced self-regulated learning behaviors and deeper engagement with character development activities. Qualitative analysis showed that students appreciated the gamification elements and found the LMS-mediated learning more engaging and meaningful. Learning analytics data indicated consistent progress tracking and timely teacher interventions. Novelty/Originality of this study: The technology-enhanced Tri Hita Karana character education model effectively develops primary students’ competencies through culturally grounded digital pedagogy. This study strengthens evidence on technology-mediated character education and shows how local wisdom supports global educational goals. It highlights the need for teacher professional development and policy support to implement culturally responsive, technology-enhanced, and sustainable blended learning in primary education.